A significant role of V5+ and V4+ with their associated oxygen species on the catalytic behaviour of vanadium phosphate catalysts for selective oxidation of n-butane to maleic anhydride - Yap, Taufiq Yun Hin (2008)
A good correlation of n-butane conversion and V4+ phase was observed. This suggested that V4+ is highly active for n-butane conversion and a minimum of ~ 10% of V4+ is necessary to activate the n-butane. MA selectivity is proportionate with the V5+ phase at lower percentage (< 30%). However, when the amount of V5+ exceeding ~ 43%, the MA selectivity will drastically dropped. High amount of V5+ phase also deteriorated the conversion of n-butane. Having excess of V5+ phase with low amount of V4+ clearly inhibits the activity of the catalyst. However, a presence of small amount of V5+ also can also enhanced the catalytic activity. TPR in H2 shows two reduction peaks which correspond to the removal of two kinetically different oxygen species i.e. O2- and O- which associated with V5+ and V4+ phases, respectively. The availability and behaviour of these oxygen species play an important role in determining the catalytic performance. A direct relationship between the amounts of oxygen removed from V4+ with the reaction rate of n-butane. The role of this oxygen species which assigned to O- contributed to the activity of the catalysts. A lower amount of oxygen species associated with V4+ removed from BiFe-doped catalysts clearly showed a poor activity of these catalysts. Correlation between percentage of V4+ and oxygen species removed associated with V4+ showed that at least 30% of V4+ is necessary to provide an active site for n-butane activation. The dependence of the n-butane conversion on the highly reactive oxygen species suggested that the released of O- anion from the surface of VPO catalyst is the rate determining step for activation of n-butane. The oxygen species associated with V5+ also showed a good correlation with the MA selectivity. However, an excess of this type of oxygen species significantly reduced the activity. The catalytic performance of the catalysts also revealed that the oxygen species ratio of O2- to O- is important to provide high activity for the catalyst. An optimal value of the ratio of O2- to O- is shown to be 0.27.